Onlay versus sublay mesh hernioplasty for paraumbilical hernia repair (Journal of Fatima Jinnah Medical University, 2019)
Background: Abdominal wall hernia surgeries are the most common procedures performed by general surgeons. Onlay and sublay mesh hernioplasty are the most popular techniques for these hernias. However, the discussion remains about the superiority of one technique over the other. This study was conducted to evaluate the outcomes of onlay and sublay mesh hernioplasty for primary paraumbilical hernia. Patients and methods: Total of 100 patients with paraumblical hernia were randomly allocated into two groups. Onlay mesh hernioplasty was performed in one group (A) and the sublay hernioplasty was done in the other group (B). Postoperative outcomes including hospital stay, infection and recurrence of hernia, were analyzed by chi square and student t-test. Results: The mean age of the patients was 43.15 years. There were 77 females and 23 males. Mean BMI was 34.4 for Group A and 35.8 kg/m2 for Group B. Mean defect size of hernia in Group A was 4.34 cm whereas in Group B it was 4.76 cm (p=0.188). Mean duration of surgery was 40.18 minutes in Group A while it was 72.54 minutes in Group B (p
Keywords: Paraumbilical hernia; Onlay; Sublay; Mesh; Hernioplasty